2013
DOI: 10.4992/jjpsy.84.130
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability factors for school stress among junior high school students: Over-adaptation and evaluation of emotion

Abstract: This study investigated the role of over-adaptation and evaluation of emotion as stress vulnerability factors among Japanese junior high school students. Based upon the diathesis-stress model, 720 students (348 boys and 372 girls) completed questionnaires about stress responses, over-adaptation, and evaluation of emotion. Two weeks later, they completed the questionnaire about stress responses along a questionnaire about school stressors. Hierarchical multiple regression analysis indicated that boys with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…First, regarding the relationship among alexithymia, perceived stress, and behavioral patterns for over-adaptation, it is reported that alexithymia individuals tend to perceive stressors more easily and experience more stress in their lives than other individuals (Goto, 2007). Furthermore, people who have experienced stress show behavioral patterns that are more adaptive to their surroundings than those who have not (Ishizu & Ambo, 2013), such that they tend to maintain a harmonious relationship with others (Miura & Agari, 2002). In other research, perceived stress has been shown to increase self-doubt (Nakashima et al, 2010;Zhao et al, 2015) and self-inhibition (Tomaka et al, 1999;Begley & Glacken, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…First, regarding the relationship among alexithymia, perceived stress, and behavioral patterns for over-adaptation, it is reported that alexithymia individuals tend to perceive stressors more easily and experience more stress in their lives than other individuals (Goto, 2007). Furthermore, people who have experienced stress show behavioral patterns that are more adaptive to their surroundings than those who have not (Ishizu & Ambo, 2013), such that they tend to maintain a harmonious relationship with others (Miura & Agari, 2002). In other research, perceived stress has been shown to increase self-doubt (Nakashima et al, 2010;Zhao et al, 2015) and self-inhibition (Tomaka et al, 1999;Begley & Glacken, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Some athletes can respond flexibly when faced with stressors ( 9 ). Conversely, people with a negative predisposition, such as those with a higher level of vulnerability, are more likely to display maladaptation when faced with a stressful event than those with a more positive predisposition ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, vulnerable individuals are more likely to develop negative interpretations of an event when faced with stress factors, resulting in the development of depression ( 15 , 16 ). Furthermore, people with a negative predisposition, for example, those with a higher level of vulnerability, are more likely to display maladaptation when faced with a stressful event than those with a more positive predisposition ( 10 ). Therefore, athletes’ level of vulnerability can affect their level of psychological distress and pain.…”
Section: Introductionmentioning
confidence: 99%
“…The term "overadaptation" is defined as the behavior of individuals who follow the expectations of others as perfectly as possible, even if their own emotions are unduly repressed. 3,4 Overadapting individuals are in a state of unbalanced internal and external adaptation; therefore, finding an approach for effectively addressing overadaptation is essential. 2 The background for this model stems from traditional observations in Japan in which many of the adolescents who develop psychiatric problems were at a younger age referred to as a "good child" who was obedient and did not frustrate the parents, 5 which may consequently lead to psychiatric problems such as mental illness, 6 obsessive symptoms, 7 and abandonment depression.…”
mentioning
confidence: 99%
“…The term “overadaptation” is defined as the behavior of individuals who follow the expectations of others as perfectly as possible, even if their own emotions are unduly repressed 3,4 . Overadapting individuals are in a state of unbalanced internal and external adaptation; therefore, finding an approach for effectively addressing overadaptation is essential 2 .…”
mentioning
confidence: 99%